2016
DOI: 10.1177/0276237416683499
|View full text |Cite
|
Sign up to set email alerts
|

Observing Individuals Viewing Art

Abstract: Understanding the mechanisms underlying the perception of artworks is of significant interest in experimental esthetics. Therefore, in this study, we utilized eye-tracking for investigating how participants familiar and unfamiliar with paintings' titles viewed Kandinsky's abstract and figural artworks. The analysis of behavioral data indicated that knowledge of the title increased participants' liking of the presented paintings and demonstrated a general preference for figural over abstract paintings. Next, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Also, participants generally liked figurative artworks with title better (Bubić, Sušac, & Palmović, 2017;Lin & Yao, 2018).…”
Section: The Role Of Contextualizing Information In Environmental Artmentioning
confidence: 99%
“…Also, participants generally liked figurative artworks with title better (Bubić, Sušac, & Palmović, 2017;Lin & Yao, 2018).…”
Section: The Role Of Contextualizing Information In Environmental Artmentioning
confidence: 99%
“…Empirical evidence of effects of additional information on aesthetic emotions is scarce. The present literature has mostly reported no effects of additional information in the form of titles on the emotional experience (Bubić et al, 2017) and interest (Leder et al, 2006;Gerger and Leder, 2015). One study considered art appreciation as a scale of interest and liking ratings together and reported significant effects of additional information (Swami, 2013).…”
Section: Art Processing Aesthetic Emotions and The Evaluation Of Artworkmentioning
confidence: 88%
“…Subsequently, we could also not show a compensating effect of explanations for interest and confusion. Research on aesthetics often reported non-significant effects of additional information, such as titles, on emotional outcomes (Bubić et al, 2017) or more specifically interest (Leder et al, 2006;Gerger and Leder, 2015). These results, however, are surprising since a close link between liking and the experience of aesthetic emotions can be assumed to be based on the models (Pelowski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not the very presence or absence of a title of an artwork that influences its greater or lesser appreciation. This depends on how it is formulated (Bubić, Sušac, & Palmović, 2017;Gerger & Leder, 2015;Leder, Carbon, & Ripsas, 2006;Millis, 2001;Thömmes & Hübner, 2014), to what extent it expresses the author's intentions (Jucker, Barrett, & Wlodarski, 2014), the level of participants' expertise (Mullennix & Robinet, 2018), whether it refers to a work of figurative or abstract art (Belke, Leder, Strobach, & Carbon, 2010;Leder et al, 2006), and even on the experimental design used (within-vs. between-participants) (Russell, 2003).…”
Section: Introductionmentioning
confidence: 99%